2007
DOI: 10.1186/1471-2393-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour versus expectant management in women with preterm prelabour rupture of membranes between 34 and 37 weeks (the PPROMEXIL-trial)

Abstract: BackgroundPreterm prelabour rupture of the membranes (PPROM) is an important clinical problem and a dilemma for the gynaecologist. On the one hand, awaiting spontaneous labour increases the probability of infectious disease for both mother and child, whereas on the other hand induction of labour leads to preterm birth with an increase in neonatal morbidity (e.g., respiratory distress syndrome (RDS)) and a possible rise in the number of instrumental deliveries.Methods/DesignWe aim to determine the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…In contrast, a more proactive or sometimes even aggressive approach may lead to a poorer neonatal outcome 15 . Currently, major randomised controlled trials are investigating the best treatment regimen for women with pPROM (PPROMEXIL study, 36 PROMPT study 37 ) and hypertensive disorders (HYPITAT II study 38 ) between 34 and 37 weeks of gestation. The outcome of these studies might influence doctors’ behaviour in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a more proactive or sometimes even aggressive approach may lead to a poorer neonatal outcome 15 . Currently, major randomised controlled trials are investigating the best treatment regimen for women with pPROM (PPROMEXIL study, 36 PROMPT study 37 ) and hypertensive disorders (HYPITAT II study 38 ) between 34 and 37 weeks of gestation. The outcome of these studies might influence doctors’ behaviour in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of labor and delivery for PPROM after 34 weeks’ gestation is recommended because, compared to expectant management, expeditious delivery is associated with reduced maternal infection and need for neonatal intensive care without any increase in perinatal morbidity and mortality [25,9697]. However there is currently wide variation in practice and additional trials are ongoing to firmly establish the benefit of induction of labor prior to 37 weeks in cases of PPROM [25,98100]. In the setting of prolonged membrane rupture (>18 hours) at term, prophylactic antibiotics are not indicated if the mother is not colonized with GBS; however the CDC recommends starting GBS prophylaxis if GBS status is unknown [101].…”
Section: Preventionmentioning
confidence: 99%
“…While there is good evidence that for term PROM early delivery is associated with a lower incidence of maternal infection and increased maternal satisfaction compared with expectant management, 43 trials of optimal management of preterm PROM are still underway. 44,45 A recent review found insufficient evidence to support planned delivery when maternal diabetes is controlled. 1 Our data did not contain information on diabetes management, but a steep increase in uncontrolled diabetes seems an unlikely explanation for an increasing proportion of planned deliveries associated with diabetes.…”
Section: 39mentioning
confidence: 99%